Research on radioactive source localization algorithm based on array detector - Li, Yan; Gao, Weichen; Yang, Bin; Li, Gang; Yang, Dazhan; Zhou, Dongliang; Zhang, Pengda (Journal of physics. Conference series, 2024)
In this paper, a ring array radiation detector based on a point kernel integral algorithm is designed for the current situation of potential radiation damage to the public after patients undergo internal radiotherapy. The detector calculates the distribution and activity of radionuclides in the body by measuring the radioactive dose of the patient’s body surface, so as to improve the scientific nature of the diagnosis and treatment effect evaluation and radiation protection strategy. Experimental verification shows that the method has high accuracy in the calculation of radioactive source activity, and can provide effective data support while simplifying the calculation amount. The work of this paper provides new technical means and a theoretical basis for precise treatment and radiation protection of nuclear medicine.